Case study: Moshi Mochis / Nor Syahdani Zulkifi ... [et al.] - Zulkifi, Nor Syahdani; Zulkiflee, Nurin Aina Nabihah; Zulkarnain, Nur Ayuni Kartini; Mohd Sufian, Nur Hadirah Sofia; Kader, Muhammad Aiman Muzamil; Tengku Baharim, Tengku Aishah Fatimah (2021)
Moshi Mochis is a business started back in October 2020. Moshi Mochis is offering a variation and customizable accessories. The product is extraordinary based on the adjustable design and the variety of option for the customer to choose from is amazingly aesthetics. The name of the business ‘Moshi Mochis’ was named by the owner itself due to the rareness, catchy as well as unique which make it more outstanding compared to the common branding name we heard. As for the marketing of the product, the owner focusing on targeting the teenagers and millennial based on the trend and colorful design. The product such as customizable glasses chain, rings, phone case and more accessories will definitely grab their attention to purchase it. Other than that, the marketing strategies that have been done by the owner is advertising the product through social media such as Facebook and Instagram as a result of the main platform used by the potential customers. Besides, promoting via special interest group such as KPOP fans, positively giving the owner opportunities to enhance the design variation as well as increasing the potential customers. Meanwhile, the pricing stated by the owner is certainly affordable for the youngster to purchase it. Last but not least, throughout the pandemic situation nowadays, the business is still ongoing due to the main platform is based on the social media and the purchasing method can be make online as well which make it more accessible and ease the productivity of the business to proceed.